Erythrina Subumbrans Compress To Reduce Fever Of Children With Hyperthermia - Alfika Awatiszahro; Betanuari Sabda Nirwana; Khofidhotur Rofiah; Putri Riga Sefika; Hidayatul Ulum (Journal of Global Research in Public Health, 2023)
Fever is one of the side effects that occur in the body when getting an attack from outside such as infections due to viruses, bacteria and others and is not the main diagnosis. The content of spare dadap leaves is saponins, flavonoids, polyphenols, tannins, and alkaloids. One of the contents of spare dadap leaves that function as antipyretics is alkaloids and ethanol. The purpose of this study was to determine the effect of spare dadap leaves on reducing body temperature in children with hyperthermy. This research design is Pre-Experimental with  a one group pre-test-post  test design which in this design allows researchers to test changes that occur after the treatment The number of samples in this study was 15 respondents.  This research was conducted from October to November 2022 at PMB Mrs. S Ngawi Regency in 2022.Statistical tests obtained p values of 0.001 < 0.05, meaning that there is an effect of spare dadap leaf compress on reducing body temperature of children with hyperthermy. Based on the results of the study, it can be concluded that spare dadap leaf compresses can be used as an alternative to reduce fever in children with hyperthermy.